La contribution de la terminologie à la conception théorique des langages documentaires et à l’indexation de documents - Mustafa-Elhadi, Widad (Meta, 1992)
AbstractThis paper attempts to show the contribution of certain linguistic phenomena, and reciprocally, the contribution of linguistics to the analysis of semantic relationships used by the documentalists in conceiving thesauri. Abstract representation of extra-linguistic reality involves understanding of certain designation processes which are useful for linguistic research. Taking into account these elements would help achieving a better collaboration between linguists, documentalists and information systems designers.